Modulation of intracellular calcium waves and triggered activities by mitochondrial ca flux in mouse cardiomyocytes. - Zhenghang Zhao; Richard Gordan; Hairuo Wen; Nadezhda Fefelova; Wei-Jin Zang; Lai-Hua Xie (PLoS ONE)
Recent studies have suggested that mitochondria may play important roles in the Ca(2+) homeostasis of cardiac myocytes. However, it is still unclear if mitochondrial Ca(2+) flux can regulate the generation of Ca(2+) waves (CaWs) and triggered activities in cardiac myocytes. In the present study, intracellular/cytosolic Ca(2+) (Cai (2+)) was imaged in Fluo-4-AM loaded mouse ventricular myocytes. Spontaneous sarcoplasmic reticulum (SR) Ca(2+) release and CaWs were induced in the presence of high (4 mM) external Ca(2+) (Cao (2+)). The protonophore carbonyl cyanide p-(trifluoromethoxy)phenylhydrazone (FCCP) reversibly raised basal Cai (2+) levels even after depletion of SR Ca(2+) in the absence of Cao (2+) , suggesting Ca(2+) release from mitochondria. FCCP at 0.01 - 0.1 µM partially depolarized the mitochondrial membrane potential (Δψ m ) and increased the frequency and amplitude of CaWs in a dose-dependent manner. Simultaneous recording of cell membrane potentials showed the augmentation of delayed afterdepolarization amplitudes and frequencies, and induction of triggered action potentials. The effect of FCCP on CaWs was mimicked by antimycin A (an electron transport chain inhibitor disrupting Δψ m ) or Ru360 (a mitochondrial Ca(2+) uniporter inhibitor), but not by oligomycin (an ATP synthase inhibitor) or iodoacetic acid (a glycolytic inhibitor), excluding the contribution of intracellular ATP levels. The effects of FCCP on CaWs were counteracted by the mitochondrial permeability transition pore blocker cyclosporine A, or the mitochondrial Ca(2+) uniporter activator kaempferol. Our results suggest that mitochondrial Ca(2+) release and uptake exquisitely control the local Ca(2+) level in the micro-domain near SR ryanodine receptors and play an important role in regulation of intracellular CaWs and arrhythmogenesis.